Associations of serum cystatin C with depressive symptoms and suicidal ideation in major depressive disorder - Ting Sun (BMC, 2021)
Abstract Background Individuals with major depressive disorder (MDD) have high suicidal ideation. There is evidence that serum cystatin C (Cys C) may be involved in the pathophysiology of MDD. The present study aimed to investigate Cys C concentration in patients with MDD and clarify its possible association with depressive symptoms and suicidal ideation. Methods An online cross-sectional survey of 159 patients diagnosed with MDD was conducted. Serum Cys C levels were measured using ADVIA 2400 biochemical analyzer. The 24-item Hamilton Depression Scale (HAMD-24) was administered to evaluate the depressive symptoms. Generalized linear regression, logistic regression and restricted cubic spline models were used to examine the association of serum Cys C levels with depressive symptoms and suicidal ideation. Results Serum Cys C levels were higher in MDD patients than in controls (p = 0.001) and were positively associated with scores on HAMD-24 in unadjusted (gender distribution, age, smoking, alcohol consumption, family history of depression and traumatic life events; (p = 0.003) and fully adjusted linear regression model (p = 0.005). The fully adjusted regression coefficient with 95% confidence intervals for serum Cys C levels and HAMD-24 score was 30.339 (9.602 to 51.077). The level of Cys C in the suicidal ideation (SI) group was significantly higher than that in the non-suicide ideation (non-SI) group (p = 0.001). Serum Cys C levels were positively associated with suicidal ideation in each logistic regression model (all p <  0.05). Conclusion Serum Cys C levels were elevated in MDD patients and appeared to be positively correlated with depressive symptoms and suicidal ideation. These findings suggest that the dysfunction of Cys C may be involved in the severity of depression and in the pathophysiological process of MDD. Thus, regulation of serum Cys C could potentially be an effective predictor of the severity of depression and potentially, play a role in reducing the risk of suicide in MDD patients.